“Falling Off a Cliff”: Mothering Disabled Children through the Pandemic and Beyond - Currie, Genevieve; Doherty Kirby, Amanda; Lebsack, Jeanine; Grahovac, Danijela; Pozniak, Kinga (Journal of the Motherhood Initiative for Research and Community Involvement, 2023)
The COVID-19 pandemic has taken a disproportionate toll on the lives of mothers of disabled children. These children have complex needs that require health, educational, and social care support services, but most of these services were cancelled or reduced because of COVID-19-related restrictions. In this article, a group of mother-researchers use a collaborative autoethnographic approach to highlight the essential role that mothers and carework play in social organization; identify gaps in services and systems due to COVID-19 policies; and provide suggestions to transform our social care support systems to better meet the needs of disabled children and their families.